Business Philosophy of the Family Micro Culinary Enterprises. A Comparative Study of the Ayam Topan and Sulam Rice Shops’ Praxis in Jababeka Bekasi: Filosofi Bisnis Usaha Kuliner Mikro Keluarga Studi Perbandingan Praktik Warung Ayam Topan dan Warung Nasi Sulam di Jababeka Bekasi - Yumarma, Andreas (Undiksha, 2024)
Along with the modern market and mall dynamic, the family micro-culinary enterprises show their existence and survival amid the strict competition and the pandemic impact. Basic principles and fundamental conceptual foundations work as a business philosophy, sustaining their existence and continuous improvement. This writing aims to discover and examine the business philosophy behind the praxis of the business activities in Family Micro Culinary Enterprises. The method of study is analytical, descriptive, phenomenological, and comparative to discover the business philosophy in practice and how it is applied in business activities. In conclusion, this writing offers a conceptual contribution to the science of the philosophy of business based on the family sma ll culinary enterprises, and some recommendations are given for the survival of the family micro culinary enterprises in the post-pandemic recovery competition.